2020
DOI: 10.17509/jpp.v20i3.25399
|View full text |Cite
|
Sign up to set email alerts
|

Critical Literacy Strategy and Challenges: Voice from a High School EFL Teacher

Abstract: This qualitative case study is proposed to investigate the implementation of critical literacy strategy in the English as a Foreign Language (EFL) classroom by one English teacher from one of the public senior high school in Indonesia. The qualitative analysis of the data collected from classroom observation and interview show that the teacher implements the five-steps instructional framework of critical literacy. In the implementation stage, the teacher conducted the framework's whole steps and emphasized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This is also supported by Setyarini, Muslim, Rukmini, Yuliasri, and Mujiyanto (2018) who claimed that HOTS might develop some of the students' knowledge such as factual, conceptual, procedural, and metacognitive knowledge that allows them to further explore the content of the text delivered. Although some studies on critical literacy had been conducted previously, the results still found that the teacherparticipants were still dependent on the materials provided in the textbook without involving students' higher order thinking skills (Hidayat, Gustine, and Setyarini, 2020). Another research conducted by Firoozi, Razavipour, and Ahmadi (2019) also supported that the EFL teachers' assessment literacy still constructed the literacy rubrics concerning language skills without focusing on the higher order thinking skills.…”
Section: Background Of the Studymentioning
confidence: 90%
“…This is also supported by Setyarini, Muslim, Rukmini, Yuliasri, and Mujiyanto (2018) who claimed that HOTS might develop some of the students' knowledge such as factual, conceptual, procedural, and metacognitive knowledge that allows them to further explore the content of the text delivered. Although some studies on critical literacy had been conducted previously, the results still found that the teacherparticipants were still dependent on the materials provided in the textbook without involving students' higher order thinking skills (Hidayat, Gustine, and Setyarini, 2020). Another research conducted by Firoozi, Razavipour, and Ahmadi (2019) also supported that the EFL teachers' assessment literacy still constructed the literacy rubrics concerning language skills without focusing on the higher order thinking skills.…”
Section: Background Of the Studymentioning
confidence: 90%
“…Although there are some themes in fairytales that are unrealistic, the overall effect is positive and offers fundamental elements for children 's development. ( Johnson, 2016) In Indonesia, research on literacy has been conducted with some different topics and discussion such as teaching media literacy strategies (Afrilyasanti et al, 2022), survey on critical literacy pedagogical approaches (Gustine, 2018), the effects of critical literacy using short stories (Halimah et al, 2020), alternative critical literacy practices in schools (Hendriani et al, 2018), and critical literacy strategies and challenges (Hidayat et al, 2020). However, none of these studies have addressed how literacy practices offer alternative understandings within an educational institution that implements them.…”
Section: Introductionmentioning
confidence: 99%
“…Yen and Halili (2015) highlighted that CT aimed to shape students' habits since they gained more exposures of being critical during their learning. Hidayat et al (2020) found that critical thinking should be integrated in language learning since students were accustomed to giving their perspectives, comments, and arguments directed to support social justices. By doing so, students eventually possessed more social awareness.…”
Section: Introductionmentioning
confidence: 99%